Illocutionary Act in Disney Pixar Movie "Soul” - Maharani, Putu Devi; Sari, Ni Putu Nilam (SPHOTA: Jurnal Linguistik dan Sastra, 2023)
This research is aimed to analyse the illocutionary act which were found in Soul movie. Movie is one of entertainment that can show the use of language in society. Speech act is the focus of this research especially in illocutionary act. By using descriptive qualitative analysis, this research is conducted. The data were collected from observation, documentation, and note taking techniques. After the data collected, the result was analysed based on the speech act theory from Searle in (Yule, 2017). Besides, theory of context of situation proposed by Halliday & Ruqaiya (1989) was used in explaining the situation happened in the story. The findings were explained by using context of situation of this research showed that there were 86 all of 5 illocutionary acts found. There were 23 Representative, 30 Directive, 12 Commissive, 19 Expressive, and 2 Declarative. The directive illocutionary act was the most speech act found in the movie. By conducting this research, it is intended to help people to understand and comprehend what message that discovered in the utterances in a movie.